ANALISIS PENGELOLAAN LIMBAH MEDIS B3 RUMAH SAKIT UMUM BOJONEGORO - Rusyda Sheffani Abbad; Khuliyah Candraning Diyanah (Universitas Airlangga, 2022)
Background: Health Service Facilities or health facilities always generate waste. The waste generated includes medical waste and non-medical waste. Waste generated by health care facilities is included in Hazardous and Toxic Waste. B3 medical waste must be managed properly in order to reduce health risks to B3 waste processing officers and the impact on the environment Objectives: The purpose of this study was to analyze the management of B3 solid medical waste at Bojonegoro General Hospital covering aspects of reduction, storage, sorting, and transportation in accordance with the Regulation of the Minister of Environment and Forestry Number 56 of 2015 concerning Procedures and Technical Requirements for the Management of Hazardous and Toxic Waste from Health Service Facilities and also to analyze officers for treating B3 solid medical waste who were exposed to B3 solid medical waste. Methods: The method used is a descriptive method with a qualitative approach Results: The result of this research is the disorganization of waste processing officers in carrying out waste management in accordance with the Regulation of the Minister of Environment and Forestry Number 56 of 2015 so that there are B3 solid medical waste processing officers who are exposed. Conclusions: B3 solid medical waste management is still not running properly, there are still some things that are not done by B3 solid medical waste processing officers Keywords: B3 medical waste, hospital, analysis